2013
DOI: 10.1002/ca.22245
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of proximal femur in patients with unilateral total hip prosthesis

Abstract: It is important to know the morphometric characteristics of the proximal femur. This is necessary to reduce the risk of complications related to surgical procedures performed in the area due to vascular, metabolic, or traumatic causes. It is of importance for achieving the alignment of the prosthesis to be implanted as well. The aim of this study was to evaluate the morphometric characteristics of the proximal femur and to establish a database for making and performing total hip prosthesis. Anteroposterior (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
(130 reference statements)
1
7
0
Order By: Relevance
“…Most of these morphometric parameters are similar to the findings in a cross-sectional study done in a tertiary hospital in Nepal. 11 The findings are also similar to that of a study done in Turkish population by Iyam C et al 13 However in the South Indian population, FNL and CDA were larger than in our study in an observational study done in cadaveric dry femur. 19 FNW and FNL in our study was larger than that found in a prospective study done in the Malay population while CDA was comparable.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most of these morphometric parameters are similar to the findings in a cross-sectional study done in a tertiary hospital in Nepal. 11 The findings are also similar to that of a study done in Turkish population by Iyam C et al 13 However in the South Indian population, FNL and CDA were larger than in our study in an observational study done in cadaveric dry femur. 19 FNW and FNL in our study was larger than that found in a prospective study done in the Malay population while CDA was comparable.…”
Section: Discussionsupporting
confidence: 91%
“…Iyam C et al reported a statistically significant difference in other parameters as well (FNL, FAL) in the Turkish population, which was not found in our study. 13 Baharuddin MY et al also reported a statistically significant difference in various parameters (FNW, FNL, CDA) between males and females in Malay population, with all parameters being larger among males. 20 In our study proximal femoral morphometry did not show any association with the BMI.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is in contrast to previous anatomical studies that have focused on open surgical or arthroplasty techniques. 10 12 , 22 , 26 The vastus tubercle has recently been qualitatively reported as a reference point for evaluation of peritrochanteric pathology. 29 The presence of the shiny white fibers of the vastus lateralis in direct continuity with this bony prominence provides a distinct and reliable reference point.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometry consisted of the following parameters: DFH -diameter of the femoral head in the cranio caudal axis (distance in a straight line from the upper end to the lower end of the femoral head) and sagittal axis (distance in a straight line from the front end behind end of the femoral head); DFN -diameter of the femoral neck in a cranio caudal axis (distance in a straight line from the upper end to the lower end of the anatomical neck of the femur) and sagittal axis (distance in a straight line, the front end to the rear end of the lap anatomy of the femur); LFN-length of the femoral neck (distance in a straight line between the lower region of the femoral head and the base of the greater trochanter) and LIL -length of the intertrochanteric line (distance in a straight line joining the highest point of trochanters highest and lowest previously (Mourao & Vasconcellos; Murlimanju et al;Iyem et al, 2013). Initially, the samples were measured with the aid of the caliper ( Fig.…”
Section: Methodsmentioning
confidence: 99%